The roles of FADD in extrinsic apoptosis and necroptosis - Lee, E.W., Yonsei University, Seoul, Republic of Korea; Seo, J.H., Yonsei University, Seoul, Republic of Korea; Jeong, M.H., Yonsei University, Seoul, Republic of Korea; Lee, S.S., Kwandong University, Gangneung, Republic of Korea; Song, J.W., Yonsei University, Seoul, Republic of Korea (BMB reports, 2012)
Fas-associated protein with death domain (FADD), an adaptor that bridges death receptor signaling to the caspase cascade, is indispensible for the induction of extrinsic apoptotic cell death. Interest in the non-apoptotic function of FADD has greatly increased due to evidence that FADD-deficient mice or dominant-negative FADD transgenic mice result in embryonic lethality and an immune defect without showing apoptotic features. Numerous studies have suggested that FADD regulates cell cycle progression, proliferation, and autophagy, affecting these phenomena. Recently, programmed necrosis, also called necroptosis, was shown to be a key mechanism that induces embryonic lethality and an immune defect Supporting these findings, FADD was shown to be involved in various necroptosis models. In this review, we summarize the mechanism of extrinsic apoptosis and necroptosis, and discuss the in vivo and in vitro roles of FADD in necroptosis induced by various stimuli.